Some Aspects of the Distribution of Microfauna in the Arctic - Hammer, Marie (ARCTIC, 1955)
Contains a study on the circumpolar distribution of the oribatids and collemboles, very small insectlike creatures of the soil. Emphasis is placed on Greenland as a possible route between the Old World and the New, for this fauna, and for fauna in general.